Adaptasi Mahasiswa Baru dengan Beban Akademik - Rahayu Safitri; Siti Nurfadhilah; Tipa Aulia Suhandi; Sri Mulyeni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to analyze the adaptation of new students to academic workload in higher education and to identify the factors that influence their success or failure. The approach used is qualitative with a literature study. Data were analyzed thematically thru the stages of reduction, display, and conclusion drawing, resulting in key patterns regarding the dynamics of new student adaptation. The results show that the majority of new students experience difficulties in their first semester, especially when the credit load exceeds 20 credits and they are faced with complex assignment demands, periodic exams, and independent time management. This condition triggers academic stress, emotional exhaustion, decreased motivation, and even burnout, contributing to the high dropout rate in the first year. On the other hand, self-efficacy and emotional intelligence have been shown to act as protective factors capable of reducing stress levels and improving the effectiveness of coping strategies. Additionally, comprehensive orientation programs, time management workshops, academic advising, and a supportive campus environment have been proven to improve retention and accelerate the adaptation process. This research concludes that the adaptation of new students is a multidimensional process that requires both personal capacity building and systemic support from the university. The proposed recommendations include phased curriculum design, the development of instrument-based adaptation counselling services, and the implementation of a continuous mentoring program to reduce the risk of adaptation failure and optimize the academic potential of new students.